Pengaruh Jenis Produk, Ukuran Produk, Kemasan Produk Terhadap Tingkat Kejenuhan Konsumen Produk Mie Instan Indomie - Siti Rodiah; Nur Hajati; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
Abstract               This research aims to: a) To know and analyze partially product type (X1), product size (X2), product packaging (X3) to consumer saturation level (Y) on Indomie instant noodle product. B) to know and analyze simultaneously product type (X1), product size (X2), product packaging (X3) to consumer saturation level on Indomie instant noodle product. This research is an explanatory research with quantitative approach. The source of this research data is the spread of questionnaires (Questionnaire) to the consumer indomie in students of the Faculty of Economics, Islamic University of Malang. The data used are primary and secondary data. This analyst is done by using SPSS program. The results of this study indicate that product type (X1), product size (X2), product packaging (X3) have an effect on consumer saturation level (Y).                Keywords: Product type, Product Size, product packaging and consumer saturation level.